PENGARUH MINAT BACA TERHADAP PRESTASI BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KEBUDAYAAN ISLAM (SKI): Rizka Alvia Habiballah dan Septiani Selly Susanti - Rizka Alvia Habiballah; Septiani Selly Susanti (JPPG : Jurnal Pengembangan Profesi Guru, 2022)
Abstrak This study aims to determine the level of interest in reading and student achievement and to determine the effect of interest in reading on student achievement in the subject of Islamic Cultural History (SKI) at MI Al-Iman Islam Way Jepara. This type of research is quantitative research. The population in this study were all students of class VI Madrasah Ibtidaiyah Al-Iman Islam Way Jepara, totaling 20 people. The research instrument used in this study was a questionnaire and observation. Data analysis was carried out with the help of the SPSS 25 program consisting of descriptive statistical analysis, data normality test and hypothesis testing. From the statistical calculation of hypothesis testing between reading interest on student achievement based on data from hypothesis testing results, it was obtained a value of R = 0.594 which showed there was a moderate correlation between reading interest and learning achievement. This is supported by the value of R Square = 0.353 or the determinant coefficient is 35%. Which means reading interest affects learning achievement by 35%, the rest is influenced by other factors. While it is known that t arithmetic is greater than t table, namely 3.136 > 2.101, it can be concluded that H0 is rejected and Ha is accepted. It can be interpreted that "There is an Influence of Reading Interest (X) on Learning Achievement (Y)".